(untitled) (Journal of Parents and Teachers, 2014)
Concepción Arenal (1820-1893) was a multi-faceted and socially sensitive woman, a woman far ahead of her time. She always tried to provide a good education for workers, women, prisoners, abandoned children and the poor. She advocated education to solve serious social situations. She concretized her pedagogical optimism in educating people first and then preparing professionals. It is undeniable that Concepción Arenal carried out an important work of awareness raising and education in favor of the marginalized sectors. In short, she proposed an education based on individual responsibility, freedom, understanding, tolerance and justice.